Problem winy i kary w twórczości Anny Mostowskiej - Urbańska, Monika (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2009)
This article deals with problem of guilt and punishment in Anna Mostowska’s novel. Although the novelist emphasized amusement character of her works, her intention was to educate and sensibilize of reader. Mostowska’s authorship is an attemption of answering questions about point and source of suffering, justness of this one to honourable people; it includes also problems connected with destiny, guilt and punishment. In this article we can discuss this problems.